(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: The surgical center is configured as a complex sector, where machines and human slive side by side, and the latter requires the efficiency of the first. High perfection and absence of errors determine a stressful environment, given that men are not machines and, although thorough hand responsible, are liable to error. It is estimated that nearly 234.2 million major surgical procedures are undertaken every year worldwide. Existing evidence suggests that seven million patients suffered surgical complications annually, 50% of which were preventable. The surgical procedure is developed by a multidisciplinary team, with different functions, but not independent, and research has shown weakness in safety Aim & Objectives: The aim of the study was to determine the effectiveness, compliance, and critical factors for the successful initiation and implementation of World Health Organization’s Safe Surgery Check list(WHO SSC)in surgical theaters in atertiary care teaching hospital. Method: The present study was an observational, prospective, and cross-sectional study conducted at Santosh Medical College and Hospital, Ghaziabad (Uttar Pradesh). The study was conducted from August2016toDecember2018. Result: Sign in was not recorded 2% of the times, time out and sign out was not recorded 2.5% of the times among all surgical procedures conducted. The major reasons were the behavioral issues (1.5%) and inadequate staff(2.0%), followed by negligence(1.5%)in our setup. Conclusion: Operating rooms are a unique environment within the healthcare system; the majority of operating room errors result from alack of communication and patient safety initiatives must focus on improving intra-operative communication.